2019
DOI: 10.3390/f10090752
|View full text |Cite
|
Sign up to set email alerts
|

Response Characteristics of Chinese Pine (Pinus tabulaeformis Carr.) Radial Growth to Climate and Drought Variability Reconstruction in Western Liaoning, Northeast China

Abstract: Chinese pine (Pinus tabulaeformis Carr.) plays an important role in maintaining ecosystem health and stability in western Liaoning Province and the southern Horqin sand land, Northeast China, with benefits including sand fixation and soil erosion. In the context of climate change, developing a better understanding of the relationship between climate factors and growth rates of this species will be extremely valuable in guiding management activities and meeting regional conservation objectives. Here, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Measurements at the leaf scale show that MP features a higher photosynthetic rate, lower transpiration rate, and higher water use efficiency than CP under favorable soil moisture conditions ( Bai et al, 2008 ; Ding et al, 2011 ). However, this trend would change under severely dry soil conditions ( Liu et al, 2019 ). Combining these pieces of information, it can be concluded that the drought stress seems to be more harmful to the needles of CP , while it imparts greater damage to the fine roots of MP .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurements at the leaf scale show that MP features a higher photosynthetic rate, lower transpiration rate, and higher water use efficiency than CP under favorable soil moisture conditions ( Bai et al, 2008 ; Ding et al, 2011 ). However, this trend would change under severely dry soil conditions ( Liu et al, 2019 ). Combining these pieces of information, it can be concluded that the drought stress seems to be more harmful to the needles of CP , while it imparts greater damage to the fine roots of MP .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CP maintains its leaf water potential at a relatively constant level of approximately −1.7 MPa by markedly reducing its leaf stomatal conductance ( Wen et al, 2017 ; Tang et al, 2018 ; Wu et al, 2018 ). Direct measurements at the leaf scale also indicate that both CP and MP may be drought-tolerant tree species with high water potential and delayed dehydration ( Tang et al, 2018 ); their leaves exhibit relatively strong water retention capacity and an ability to maintain turgor ( Ding et al, 2011 ; Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pinus tabulaeformis Carr., a coniferous evergreen tree of Pinaceae, is characterized by a well-developed root system, rapid growth, strong ecological adaptability and stress resistance and is a pioneer tree for vegetation restoration in a variety of stress environments (Liu et al, 2019;Zeng et al, 2020). Research has found that there are a variety of ectomycorrhizal fungi in the roots of P. tabulaeformis (Hibbett and Matheny, 2009;Wang and Guo, 2010).…”
Section: Introductionmentioning
confidence: 99%